Cone Beam Computed Tomography Evaluation of the Diagnosis, Treatment Planning, and Long-Term Followup of Large Periapical Lesions Treated by Endodontic Surgery: Two Case Reports - Shekhar, Vijay (Hindawi Publishing Corporation, 2013)
The aim of this case report is to present two cases where cone beam computed tomography (CBCT) was used for the diagnosis, treatment planning, and followup of large periapical lesions in relation to maxillary anterior teeth treated by endodontic surgery. Periapical disease may be detected sooner using CBCT, and their true size, extent, nature, and position can be assessed. It allows clinician to select the most relevant views of the area of interest resulting in improved detection of periapical lesions. CBCT scan may provide a better, more accurate, and faster method to differentially diagnose a solid (granuloma) from a fluid-filled lesion or cavity (cyst). In the present case report, endodontic treatment was performed for both the cases followed by endodontic surgery. Biopsy was done to establish the confirmatory histopathological diagnosis of the periapical lesions. Long-term assessment of the periapical healing following surgery was done in all the three dimensions using CBCT and was found to be more accurate than IOPA radiography. It was concluded that CBCT was a useful modality in making the diagnosis and treatment plan and assessing the outcome of endodontic surgery for large periapical lesions.